1984
DOI: 10.1523/jneurosci.04-01-00001.1984
|View full text |Cite
|
Sign up to set email alerts
|

Regional innervation of rabbit ciliary ganglion cells by the terminals of preganglionic axons

Abstract: In the rabbit, ciliary ganglion neurons with dendrites maintain inputs from several different axons during the period of synaptic rearrangement that occurs in early postnatal life. Neurons without dendrites, on the other hand, lose the majority of their initial inputs and are innervated in maturity by the terminals of only one or two axons (Purves, D., and R.I. Hume (1981) J. Neurosci. 1: 441-452; Hume, R.I., and D. Purves (1981) Nature 293: 469-471). We have explored the basis of this phenomenon by individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 6 publications
2
28
0
Order By: Relevance
“…complexity of its dendrites (Purves and Hume, 1981;Purves and Lichtman, 1985). Competition between axons innervating a cell with no dendrites generally results in a single dominant input in maturity; in contrast, competition on cells with dendrites is mitigated so that an increasing number of inputs is retained on increasingly complex cells Purves, 1981, 1983;Forehand and Purves, 1984). The results of the present study show that the distribution of synapses on target neurons is also influenced by the presence of dendrites.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…complexity of its dendrites (Purves and Hume, 1981;Purves and Lichtman, 1985). Competition between axons innervating a cell with no dendrites generally results in a single dominant input in maturity; in contrast, competition on cells with dendrites is mitigated so that an increasing number of inputs is retained on increasingly complex cells Purves, 1981, 1983;Forehand and Purves, 1984). The results of the present study show that the distribution of synapses on target neurons is also influenced by the presence of dendrites.…”
Section: Discussionmentioning
confidence: 54%
“…Since the cell body is the final common pathway for all ganglion cell activity, asynchronous activity generated by the several different inputs to more complex ganglion cells may limit the ability of synapses from different axons to coexist on the cell body surface. Conversely, synapse formation on dendrites might be less affected by increased convergence because dendrites are innervated by only a subset of the inputs to a particular ganglion cell (Forehand and Purves, 1984) and are to some extent isolated from each other by the passive electrical properties of the dendritic arbor.…”
Section: Density Of Dendritic Synapses On Mammalian Superior Cervicalmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that the transmitter action was augmented by a regenerative conductance change initiated distal from the soma. We propose that this results because the synaptic contacts of the strong preganglionic axon exist on a single dendrite (see Forehand & Purves, 1984) and are associated with the region of the membrane containing voltage-dependent calcium channels. Activation of this input invariably evokes an action potential in the ganglion cell when it is not hyperpolarized.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, repeated imaging of developing neuromuscular junctions in the snake indicates that competing terminals tend to segregate (Balice-Gordon & Lichtman, 1989). This phenomenon may also occur (although quite incompletely) during the initial innervation of developing autonomic ganglion cells Forehand & Purves, 1984;Forehand, 1987).…”
mentioning
confidence: 99%